Modified polydimethylsiloxane / polyethersulfone composite membrane, preparation method and application thereof
By using free radical copolymerization reaction modified PDMS and polyethersulfone composite film technology in oxygenated film materials, the problems of insufficient mechanical strength and low CO2/O2 selectivity of oxygenated film materials are solved, and high-efficiency gas exchange and anti-pollution are achieved Performance oxygenated film material suitable for ECMO systems.
Patent Information
- Application Number
- CN202310326290.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-03-30
AI Technical Summary
The existing oxygenated membrane materials have problems in biological applications, including insufficient mechanical strength, low CO2/O2 selectivity, and surface hydrophobicity, which limits their application in ECMO systems.
Using free radical copolymerization modified polydimethylsiloxane (PDMS) material, combined with polyether sulfone (PES) as the porous support layer and dense functional layer of the composite film, optimized by phase conversion and wet coating film preparation method The hydrophobicity of the PDMS surface and enhances its mechanical strength.
The composite membrane material with high CO2/O2 selectivity, gas permeability and anti-pollution properties has been achieved, which improves gas flux and mechanical strength, reduces leakage problems of gas plugs and material liquids, and is suitable for biomedical applications.
Smart Images

Figure CN116272449B_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly focuses on the separation process of different components in gas-liquid two-phase in the biological field, and studies the preparation and application of membrane materials used in the process. For the separation of different gas components in gas-liquid two-phase medium, an innovative preparation method of modified PDMS / PES composite membrane material is proposed. The porous support layer of the composite membrane mainly adopts polyethersulfone (PES), and the separation functional layer adopts modified polydimethylsiloxane (PDMS), so as to achieve the separation of O in the two-phase medium. 2 and CO 2 Separation exchange. Background Art
[0002] Extracorporeal membrane oxygenation (ECMO) is an ex vivo life support system that uses an artificial polymer membrane (i.e., oxygenation membrane) to achieve oxygen and carbon dioxide exchange in the venous blood of patients with severe cardiopulmonary failure or organ transplantation. ECMO was first reported in 1974 and has provided effective auxiliary support for tens of thousands of patients. As the core component of the ECMO system, the oxygenation membrane is in direct contact with the patient's blood and should have efficient oxygen and carbon dioxide gas exchange capabilities and good blood compatibility. The membrane also requires a certain mechanical strength to withstand the shear force generated by blood circulation. According to Valencia E, in "Updates in Pediatric Extracorporeal Membrane Oxygenation-ScienceDirect", poly (4-methyl-1-pentene) (PMP) is currently the most widely used commercial oxygenation membrane material. Synthetic PMP polymer is a semi-crystalline non-polar polyolefin resin with the lowest density among all thermoplastic polymers used in medical applications. At the same time, PMP also has excellent heat resistance, chemical resistance and low surface tension, which makes it a good candidate for oxygenation membranes in ECMO systems. However, due to the small density difference between the irregular crystalline and amorphous regions of PMP and the small pore size, it is difficult to make membranes using PMP. In addition, the PMP asymmetric membrane with a dense PMP layer coated on a porous PMP substrate has a lower CO 2 Permeability and CO 2 / O 2 Selective.
[0003] So far, polyethersulfone (PES), polysulfone (PSF), polyacrylonitrile (PAN), polyimide (PI), etc. have become common materials for preparing gas separation membrane support layers due to their excellent tensile properties, hydrophobicity, porosity, temperature resistance and corrosion resistance. However, due to the surface physical and chemical properties of the material itself, it does not have good biocompatibility in biological applications. Polydimethylsiloxane (PDMS) is a widely used silicone material. It is composed of alternating Si-O bonds to form a main chain, and its spatial structure is helical. Due to its physical and chemical properties such as good biocompatibility, certain elasticity, heat resistance, stable chemical inertness and easy availability of raw materials, it is widely used in many fields such as special materials for aerospace, building materials, and biomedical related materials. The structural formula of PDMS is shown below.
[0004]
[0005] Bilal Haider et al. mentioned in "Highly permeable innovative PDMS coated polyethersulfone membranes embedded with activated carbon for gas separation" that a separation membrane with PDMS as the functional layer and PES membrane as the supporting layer was prepared, and its carbon dioxide gas permeability was 281.34GPU and Young's modulus reached 248.71MPa. PES has become a potential supporting layer due to its comprehensive properties such as high mechanical strength, high heat resistance and excellent alkali resistance. Abdul Latif Mohtada Sadrzadeh mentioned in "Gas permeation through a synthesized composite PDMS / PES membrane" that a PDMS / PES composite membrane was prepared. The material has good gas permeability and certain mechanical strength, but the hydrophobicity of the surface of the prepared composite membrane will lead to severe protein adhesion and thrombosis, which makes it subject to certain restrictions in the application process. The composite membrane is prepared by using PDMS as a dense cortex and a porous PES membrane material as a supporting base membrane. The dense cortex can effectively prevent leakage during gas-liquid separation. And the thinner skin, in its special high CO 2 / O 2Under selectivity, the film thickness of the dissolution diffusion layer can be reduced, thereby increasing the gas flux. The PDMS material itself is soft, and PES can provide good mechanical support in the gas-liquid classification process. However, due to the hydrophobic structure on the surface of PDMS, when it is used as a biomaterial, non-specific adsorption of proteins or cell adhesion will occur, thereby causing material pollution. The present invention introduces hydrophilic groups into the PDMS polymer through free radical copolymerization, thereby improving the hydrophobic structure of the surface of PDMS as a functional coating. Summary of the invention
[0006] The present invention proposes a simple modification method for the application limitation of the above-mentioned PDMS material, which adopts a free radical copolymerization reaction to modify PDMS with 2-hydroxyethyl methacrylate in a nitrogen atmosphere. The PES base film is used as the composite membrane support material of the modified PDMS, and the PES material has stable physical and chemical properties, is non-toxic, does not change its composition when in contact with gas and liquid phases, and meets the processing procedures for use of biomedical materials. The present invention uses a method for preparing a composite membrane by phase inversion and wet coating, which successfully solves the problem that the PDMS material itself is soft. At the same time, the modified PDMS can improve the hydrophobic structure on its surface, and as a coating, the film layer is thinner and can achieve good gas permeability.
[0007] The technical solution of the present invention:
[0008] A modified polydimethylsiloxane / polyethersulfone composite membrane, wherein polyethersulfone is a porous support layer of the composite membrane; PDMS modified by free radical copolymerization is a functional layer; PDMS is reacted under a nitrogen atmosphere, and then cross-linked and configured, and the treated modified PDMS coating liquid is dip-coated on a pre-prepared polyethersulfone base membrane. The modified PDMS is used as a separation coating in the composite membrane, and its thickness can be controlled by dip-coating. The cross-section of the polyethersulfone as a base membrane is a loose finger-like pore structure with a large cavity inside and micropores on its dark surface. The modified PDMS as a functional coating is relatively dense and has a smooth surface.
[0009] A method for preparing a modified polydimethylsiloxane / polyethersulfone composite membrane, comprising the following steps:
[0010] (1) PES porous support layer: using the phase inversion method, N,N-dimethylformamide (DMF) was used as the solvent, 15 wt% PES and 5 wt% polyethylene glycol (PEG) were added to the total solution, PEG was used as the pore-forming agent, and the base film solution was prepared. The solution was ultrasonically placed for 2 h. The film was scraped using a desktop flat film scraping machine. After the scraping was completed, the film was immersed in deionized water for 24 h for phase inversion to obtain a PES porous support layer.
[0011] (2) Free radical copolymerization modification of PDMS: PDMS was dissolved in isooctane, and then 2-hydroxyethyl methacrylate (HEMA) was added, and the mass ratio of 2-hydroxyethyl methacrylate to PDMS was 1:0.9; then 1 mol% of azobisisobutyronitrile (AIBN) and 1.5 mol% of N,N-methylenebisacrylamide (MBA) (relative to HEMA) were added, and the mixed solution was placed in a nitrogen atmosphere, reacted at 85°C for 5 hours, and then allowed to cool;
[0012] (3) PDMS dense functional layer coating: First, add the crosslinker and catalyst to the modified PDMS solution, and the mass ratio of PDMS, crosslinker and catalyst is 100:40:4. At the same time, in order to prevent PDMS from over-crosslinking and agglomeration gel, the crosslinker and catalyst should be added drop by drop slowly. After ultrasonic degassing, pour the mixed coating liquid into the coating tank, and dip-coat the coating liquid on the smoother side of the PES porous support layer. The coating time is 2-3s, and there are no bubbles between the PES porous support layer and the coating liquid, so that a uniform liquid film is formed on the surface of the PES porous support layer. Then, the coated membrane is placed in an oven at 85°C for 2h and flattened to obtain a modified polydimethylsiloxane / polyethersulfone composite membrane.
[0013] The modified polydimethylsiloxane / polyethersulfone composite membrane is applied to the gas-liquid interface and used as a membrane material for gas exchange.
[0014] Beneficial effects of the present application: The present invention is mainly used for preparing 2 / O 2 Organic composite membrane materials with selectivity, certain gas permeability and anti-pollution performance. First, a polyethersulfone membrane material with certain mechanical strength is prepared by a phase inversion method. As the base membrane of the composite membrane, it can provide certain support for the functional layer membrane material with poor mechanical properties, thereby changing the limitations of the functional coating material itself. PDMS is modified by free radical copolymerization to optimize the application limitations of its surface hydrophobicity. The thickness of the separation functional layer is regulated by wet coating to obtain a larger gas flux. In addition, the modified PDMS coating can be used as a dense membrane material to improve the problems of gas embolism and liquid leakage during the application of the composite membrane. The preparation method effectively retains the separation performance of PDMS while enhancing its mechanical strength for application. In addition, the raw materials of the present invention are easily available and inexpensive, making the large-scale application of the method possible. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1The following are SEM spectra of PDMS / PES composite membrane and modified PDMS / PES composite membrane. Figure (a) is the cross-sectional SEM image of the base membrane PES; Figure (b) is the surface morphology of the prepared base membrane PES; Figure (c) is the surface morphology of the PDMS / PES composite membrane; Figure (d) is the cross-sectional SEM image of the PDMS / PES composite membrane; Figure (e) is the surface morphology of the modified PDMS / PES composite membrane; Figure (f) is the cross-sectional SEM image of the modified PDMS / PES composite membrane.
[0016] Figure 2 is the Fourier infrared spectrum of the prepared modified PDMS / PES composite membrane.
[0017] Figure 3 The hydrophilicity and hydrophobicity test diagrams of the PDMS / PES composite membrane and the prepared modified PDMS / PES composite membrane are shown in Figure (a) and Figure (b) respectively.
[0018] Figure 4 is the CO of modified PDMS / PES composite membrane under different pressures 2 Gas permeability and CO 2 / O 2 Selectivity diagram. Figure (a) shows the CO of the modified PDMS / PES composite membrane under different pressures. 2 Gas permeability and CO 2 / O 2 Schematic diagram of selectivity change; (b) The figure shows the CO of PDMS / PES composite membrane under different pressures 2 Gas permeability and CO 2 / O 2 Schematic diagram of selective changes. DETAILED DESCRIPTION
[0019] The present invention is described in more detail and clarity below through specific implementation methods.
[0020] Embodiment 1:
[0021] A method for preparing a modified PDMS / PES composite membrane comprises the following steps:
[0022] (1) Preparation of PES porous support base membrane: PES was dried in an oven at 120°C for 12 h before use. 9 g PES, 3 g PEG and 48 g DMF were used to prepare a base membrane casting solution with 15 wt% PES and 5 wt% PEG as a pore-forming agent. The casting solution was ultrasonically treated and allowed to stand for 2 h. A desktop flat film scraper was used for film scraping. After the film was scraped, it was immersed in deionized water for 24 h for phase inversion to obtain a PES base membrane material.
[0023] (2) Free radical copolymerization modification of PDMS: 2.7 g of PDMS was dissolved in 90 ml of isooctane solution, and then 2.454 g of HEMA, 0.03026 g of AIBM (1 mol% relative to HEMA), and 0.04365 g of MBA (1.5 mol% relative to HEMA) were added dropwise. The mixed solution was placed under a nitrogen atmosphere and reacted at 85°C for 5 h, and then allowed to cool.
[0024] (3) PDMS dense functional layer coating:
[0025] First, add 1.08g of cross-linking agent and 0.108g of catalyst to 90ml of modified PDMS solution, so that the mass ratio of modified PDMS to cross-linking agent and catalyst is 100:40:4. At the same time, in order to prevent PDMS from over-cross-linking and agglomeration gel, the cross-linking agent and catalyst should be slowly added drop by drop in sequence. Pour the mixed coating liquid into the coating tank after ultrasonic degassing, and then immerse the smooth side of the PES porous support base membrane in the coating liquid so that the coating liquid is evenly coated on the surface of the PES base membrane. The coating time is about 2-3s, and there are no bubbles between the base membrane and the coating liquid. Then, the coated membrane is placed in an oven at 85°C for 2h and flattened to obtain a modified PDMS / PES composite membrane.
[0026] Embodiment 2:
[0027] A method for preparing a modified PDMS / PES composite membrane control group PDMS / PES composite membrane material comprises the following steps:
[0028] (1) Preparation of PES porous support base membrane: PES was dried in an oven at 120°C for 12 h before use. 9 g PES, 3 g PEG and 48 g DMF were used to prepare a base membrane casting solution with 15 wt% PES and 5 wt% PEG as a pore-forming agent. The casting solution was ultrasonically treated and allowed to stand for 2 h. A desktop flat film scraper was used for film scraping. After the film was scraped, it was immersed in deionized water for 24 h for phase inversion to obtain a PES base membrane material.
[0029] (2) PDMS dense functional layer coating: First, 2.7g PDMS was dissolved in 90ml isooctane and a uniform solution was obtained under magnetic stirring. Then, 1.08g cross-linking agent and 0.108g catalyst were added to make the mass ratio of PDMS to cross-linking agent and catalyst 100:40:4. At the same time, in order to prevent PDMS from excessive cross-linking and agglomeration gelation, the cross-linking agent and catalyst should be added drop by drop slowly. After ultrasonic degassing, the uniformly mixed coating liquid was poured into the coating tank, and the modified PDMS coating liquid was dip-coated on the smoother side of the porous support layer PES base membrane. The coating time was about 2-3s, and there were no bubbles between the base membrane and the coating liquid, so that a uniform liquid film was formed on the surface of the PES base membrane. Then, the coated membrane material was placed in an oven at 85°C for 2h and flattened to obtain a PDMS / PES composite membrane.
[0030] Embodiment 3:
[0031] In order to measure the pure gas permeability of the prepared composite membrane, a total of 4 modified PDMS / PSF composite membranes with different coating liquid concentrations were prepared as experimental materials using the method of Example 1(1). The specific implementation scheme is shown in the following table.
[0032] Table 1 Detailed preparation of 1%-4% modified PDMS coating solution
[0033]
[0034] Composite membrane material characterization:
[0035] 1. The modified PDMS / PES composite membrane prepared in Example 1 and the PDMS / PES composite membrane prepared in Example 2 were characterized by field emission scanning electron microscopy. First, the composite membrane was quenched at low temperature by liquid nitrogen to observe the cross-sectional morphology of the composite membrane material. The treated composite membrane material was fixed on the sample stage with conductive glue, and the surface and cross-sectional morphology were observed after current sputtering and gold spraying.
[0036] 2. The characteristic functional groups of PDMS / PES composite membrane and modified PDMS / PES composite membrane were characterized by Fourier transform infrared spectrometer ATR.
[0037] 3. Fix the PDMS / PES composite membrane and modified PDMS / PES composite membrane materials on the test bench with tape, use a microsampler to slowly drip deionized water on the surface of the material, collect three different tangent points, and obtain the hydrophilicity test results of the material through circle fitting calculation.
[0038] 4. Use the gas permeability test device to measure the pure gas permeability of the composite membrane material. Place the composite membrane in the gas test device to keep the test membrane area consistent and control the water bath temperature. Pressurize the coating to maintain the transmembrane pressure at 0.1-0.5MPa. Purge the upper and lower gas paths of the pipeline with pure gas to ensure that the pipeline gas is a single flowing gas. Use a soap bubble flowmeter to test CO 2 and O 2 Gas permeability. i Use GPU (1GPU=10 -6 cm 3 / cm 2 The permeation rate expressed in s cmHg) is determined by the following equation:
[0039]
[0040] Where J is the gas permeability, GPU; ΔV is the volume of gas passing through the flow meter, which is 3 cm 3 ; T is room temperature 25°C; A is the membrane area, calculated to be 11.34 cm 2 ; t is the time for gas to pass through the flowmeter, s; Δp is the test pressure difference, MPa. Each data is measured 3 times in parallel and the average value is taken.
[0041] Material characterization results analysis:
[0042] 1. Through the electron microscope scanning image, it can be seen that Figure 1 As shown in (a), the PES base membrane has a loose finger-like pore structure. During the phase transformation process of the base membrane liquid, most of the solvent in the membrane liquid is dissolved in water, and the solute contacts the water, resulting in a large cavity at the bottom of the composite membrane. Figure 1 As shown in (b), there are a large number of microporous structures on the surface of the PES base membrane, which form through holes with the finger-like cavity structure inside the base membrane. Figure 1 As shown in (c), the surface morphology of the composite membrane material shows that the surface of the dense layer PDMS is smooth and flat, indicating that a uniform and stable functional coating can be formed between PDMS and the base membrane PES through cross-linking. Figure 1 (d) The upper surface of the PDMS / PES composite membrane has a thin dense layer, which is cross-linked with the upper part of the base membrane to form a separation functional layer. Figure 1 (e) It is concluded that the surface of the composite membrane after modified PDMS coating is smooth and flat, without defects and rough structures. Figure 1 (f) The upper surface of the modified PDMS / PES composite membrane has a thin modified PDMS dense layer, which is cross-linked with the upper part of the base membrane to form a modified PDMS separation functional layer.
[0043] 2. Characterization of the characteristic functional groups of PDMS / PES composite membrane and modified PDMS / PES composite membrane showed that the modified PDMS / PES composite membrane had a -1 1744cm -1 The characteristic peaks of C=C, COOR and NCOOR appeared at , indicating that PDMS was modified and the composite membrane was successfully prepared.
[0044] 3. The contact angle test of the modified PDMS / PES composite membrane prepared in Example 1 and the PDMS / PES composite membrane prepared in Example 2 was performed. Figure 3 As shown, the contact angle of the PDMS coating membrane of Example 2 is 117°, which is determined by the hydrophobic structure of the surface of the PDMS dense layer of the composite membrane, while the contact angle of the modified PDMS / PES composite membrane of Example 1 is 35°, which changes the original hydrophobicity of the composite membrane material, thereby improving the adhesion and pore blockage caused by hydrophobicity during the application process, thereby increasing the service life and allowing the application product to be used for a long time.
[0045] 4. Figure 4 (a) is a modified PDMS / PES composite membrane prepared by the method of Example 1 2 Gas permeability and CO 2 / O 2 Selectivity diagram, from which it can be seen that its maximum permeability reaches about 2475GPU. As the pressure increases, CO 2 The permeability increases, CO 2 / O 2 The selectivity remains around 6.5. Figure 4 (b) CO of the PDMS / PES composite membrane prepared by Example 2 2 Gas permeability and CO 2 / O 2 Selectivity diagram, from which we can see that its CO 2 / O 2 The selectivity is lower than that of the modified PDMS / PES composite membrane at different pressures.
[0046] The present invention uses a composite membrane to regulate the base membrane and the selective layer separately. The presence of the base membrane provides mechanical support for the coating of the modified PDMS layer, and the modified PDMS layer provides good selectivity for the gas-liquid two-phase separation process. At the same time, the gas permeability and hydrophilicity and hydrophobicity of the prepared composite membrane are effectively improved after testing. The base membrane and coating materials used are relatively cheap, and can be self-produced and self-sufficient in China, without any technical barriers. It provides technical support for the preparation of special membrane materials in my country and the research and development of downstream related application equipment.
Claims
1. A method for preparing a modified polydimethylsiloxane / polyethersulfone composite membrane, characterized in that: In the modified polydimethylsiloxane / polyethersulfone composite membrane, polyethersulfone is a porous support layer, and PDMS modified by free radical copolymerization is a functional layer; the steps are as follows: (1) PES porous support layer: using the phase inversion method, N,N-dimethylformamide as solvent, adding 15wt% PES and 5wt% PEG in the total solution, using PEG as a pore-forming agent, preparing a base film solution, and ultrasonically placing it for 2 hours; using a desktop flat film scraping machine for scraping, and after the scraping is completed, immersing it in deionized water for 24 hours for phase inversion to obtain a PES porous support layer; (2) Free radical copolymerization modification of PDMS: PDMS was dissolved in isooctane, and then 2-hydroxyethyl methacrylate was added, with the mass ratio of 2-hydroxyethyl methacrylate to PDMS being 1:0.9; 1 mol% of azobisisobutyronitrile and 1.5 mol% of N,N-methylenebisacrylamide were added relative to 2-hydroxyethyl methacrylate, and the mixed solution was placed in a nitrogen atmosphere, reacted at 85°C for 5 hours, and then allowed to stand and cool to obtain a modified PDMS solution; (3) PDMS dense functional layer coating: First, add the crosslinking agent and catalyst to the modified PDMS solution in sequence, and the mass ratio of PDMS, crosslinking agent and catalyst is 100:40:
4. Pour the mixed coating liquid into the coating tank after ultrasonic degassing. Dip-coat the coating liquid on the smoother side of the PES porous support layer. The coating time is 2-3s, and there are no bubbles between the PES porous support layer and the coating liquid. A uniform liquid film is formed on the surface of the PES porous support layer. Then, place the coated membrane in an oven at 85°C for 2h and flatten it to obtain a modified polydimethylsiloxane / polyethersulfone composite membrane.
2. The preparation method according to claim 1, characterized in that: To prevent PDMS from over-crosslinking and forming agglomerated gel, the crosslinking agent and catalyst were added dropwise in sequence.
3. The modified polydimethylsiloxane / polyethersulfone composite membrane obtained by the preparation method according to claim 1 or 2 is applied to the gas-liquid interface as a membrane material for gas exchange.
